Caracterización de pacientes con hidrocefalia atendidos en el Hospital Universitario San Rafael de Tunja. 2018 - Guezguan Pérez, Jonathan Alexander; Vargas Rodríguez, Ledmar Jovanny; Muñoz Torres, Laura Daniela; Ríos Forero, Silvia Juliana; Farfán López, María Fernanda; Cuchanga Cárdenas, Carlos Fernando; Alexander García, Danny Steven (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2022)
Introduction: Hydrocephalus is a pathological, frequent and complex entity, characterized by an increase in ventricular size, generated by an accumulation of cerebrospinal fluid in the subarachnoid and ventricular spaces. Life-threatening neurological injury, the product of multiple etiologies. Objective: to characterize patients with hydrocephalus treated at the San Rafael de Tunja University Hospital, during 2018. Methodology: observational, descriptive, cross-sectional study of a retrospective historical cohort, included: patients treated at the San Rafael de Tunja University Hospital, in 2018, with a diagnosis of hydrocephalus identified by the international disease codes (ICD-10). Results: the average number of days of hospital stay was 38.1, a higher frequency of communicating and acquired hydrocephalus was observed; within the clinical manifestations predominated headache and emesis, for the diagnosis in most cases computed tomography was used, all patients required surgical management. 15.55% of the patients presented at least one complication related to the management administered, finally, it was observed that 87.77% of the people presented some sequelae. A mortality of 11.39% was documented. Conclusions: Hydrocephalus is a clinical condition of varied etiology and that can occur at all stages of life, with a known pathophysiology and heterogeneous clinical presentations, of complex medical management